2020
DOI: 10.1038/s41598-020-72158-5
|View full text |Cite
|
Sign up to set email alerts
|

A high throughput screening system for studying the effects of applied mechanical forces on reprogramming factor expression

Abstract: Mechanical forces are important in the regulation of physiological homeostasis and the development of disease. The application of mechanical forces to cultured cells is often performed using specialized systems that lack the flexibility and throughput of other biological techniques. In this study, we developed a high throughput platform for applying complex dynamic mechanical forces to cultured cells. We validated the system for its ability to accurately apply parallel mechanical stretch in a 96 well plate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The stretch plate, with ANSI standard plate contour dimensions, is automation compatible for easy integration into screening systems to facilitate high throughput endpoints such as target ID and drug discovery. While other stretch devices have been developed previously for high throughput and screening, [103][104][105][106][107] the current 192w stretch plate is of higher well capacity than other reported 96-well format systems and provides this screening advantage. Moreover, the stretch plate silicone elastomer resin design could facilitate large scale injection-molding manufacturing for rapid production and bolster high throughput research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stretch plate, with ANSI standard plate contour dimensions, is automation compatible for easy integration into screening systems to facilitate high throughput endpoints such as target ID and drug discovery. While other stretch devices have been developed previously for high throughput and screening, [103][104][105][106][107] the current 192w stretch plate is of higher well capacity than other reported 96-well format systems and provides this screening advantage. Moreover, the stretch plate silicone elastomer resin design could facilitate large scale injection-molding manufacturing for rapid production and bolster high throughput research.…”
Section: Discussionmentioning
confidence: 99%
“…The chondrocyte stretch gene signature, characterized by L1000 gene expression profiling and RASL-seq, and with adequate intra-plate consistency relative to static gene expression, illustrates feasibility of utilizing transcriptional readouts with this system. Alternative stretch readouts, such as protein expression, 103,107 cell proliferation, 17,108 morphological alignment with stretch, 104,106,109 or calcium signaling, 110 may also be employed.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously created a high throughput device that applies mechanical stretch to cancer cells in a 6 Ă— 96 well format 18 – 21 . Cells were cultured on custom 96-well culture plates with a flexible silicone membrane culture surface.…”
Section: Materials and Methods (Online)mentioning
confidence: 99%
“…20 It is, however, less clear how mechanical stretch of the flexible substrate leads to forces on the nucleus. In recent studies from our laboratory, we have found that physiological waveforms of stretch can lead to differential responsiveness of many cell types, 21,22 and in mesenchymal stem cells (MSCs), lead to increased vascular phenotypes and regenerative properties. 23 In the these studies, we demonstrated that a very specific types of mechanical stretch induce the MSCs into the vascular phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…This study provides a computational model for understanding the forces that different regions of the cells are experiencing when they are stretched at various levels of culture membrane strain. As our previous work has highlighted the importance of physiological waveforms, [21][22][23] we examined the differences between the standard sine waveform and a brachial waveform of mechanical stretch that mimics the stretch of the brachial artery during the cardiac cycle. Our previous study demonstrated that brachial waveforms delivered at 0.1 Hz frequency of loading and 7.5%-12.5% maximal strain resulted in MSCs with enhanced vascular regenerative properties and maximal activation of Yap/Taz (Yes-associated protein/transcriptional coactivator with PDZ-binding motif) signaling.…”
Section: Introductionmentioning
confidence: 99%